2015
DOI: 10.1097/jcn.0000000000000178
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function in Heart Failure Is Associated With Nonsomatic Symptoms of Depression But Not Somatic Symptoms

Abstract: Background Patients with heart failure (HF) have high rates of cognitive impairment and depressive symptoms. Depressive symptoms have been associated with greater cognitive impairments in HF; however, it is not known whether particular clusters of depressive symptoms are more detrimental to cognition than others. Objective To identify whether somatic and/or nonsomatic depressive symptom clusters were associated with cognitive function in persons with HF. Methods Participants were 326 HF patients (40.5% fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…The broad aims of the parent Heart ABC study were to examine cognitive function, psychosocial, and physical factors as predictors of adherence in patients with HF. Other reports from this study have been published examining cognitive screening methods in HF 20 and the relationship between cognition and other variables (e.g., body mass index, 21 depression, 22 quality of life, 23 and adherence behaviors 24 ).…”
Section: Methodsmentioning
confidence: 97%
“…The broad aims of the parent Heart ABC study were to examine cognitive function, psychosocial, and physical factors as predictors of adherence in patients with HF. Other reports from this study have been published examining cognitive screening methods in HF 20 and the relationship between cognition and other variables (e.g., body mass index, 21 depression, 22 quality of life, 23 and adherence behaviors 24 ).…”
Section: Methodsmentioning
confidence: 97%
“…Studies have been conducted to assess the impact of the association between HF and depression symptoms. A survey of 348 participants with a mean age of 68 years, recruited from urban medical centers, revealed that the Body Mass Index (BMI) is closely related to depressive symptoms in patients with HF, especially among women (21) . In patients with HF, depression can represent an independent risk factor for mortality and hospitalization, and is associated with higher cognitive impairment (21)(22) .…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the items have a common function, as indicators of risk, though each domain assesses a distinct aspect of functioning as it pertains to self‐care (Cameron et al., ). Second, physical, cognitive and emotional limitations may be interdependent in the context of HF, with physical limitations affecting the cognitive and emotional well‐being of patients (Alosco, Spitznagel, Cohen, et al., ; Alosco, Spitznagel, Sweet, et al., ; Hawkins et al., ). For example, the physiological changes induced by HF can compound pre‐existing issues with memory and concentration and even precipitate cognitive impairment (Cannon, McMurray, & Quinn, ).…”
Section: The Studymentioning
confidence: 99%